Sputtered Si and Mg doped hydroxyapatite for biomedical applications - Vladescu, Alina; Mihai Cotrut, Cosmin; Ak Azem, Funda; Bramowicz, Miros aw; Pana, Iulian; Braic, Viorel; Birlik, Isil; Kiss, Adrian; Braic, Mariana; Abdulgader, Radwan; Booysen, Robin; Kulesza, S awomir; et al. (Biomedical materials (Bristol), 2018)
Hydroxyapatite (HAP) coatings are applied on metallic implant materials to combine mechanical properties of metallic material with bioactivity abilities of HAP ceramic. In this study, HAP coatings with additions of Si and Mg are proposed to be deposited on Ti6Al4V substrates by RF magnetron sputtering. Chemical bonding, morphology, topography and corrosion resistance in simulated body fluids (SBF) of the coatings were investigated. Additionally, mechanical and biological properties of the coatings were evaluated. It was found that the addition of Si and Mg does not influence the formation of a HAP phase. All the coatings exhibited smooth surface and uniform growth, without defects or cracks. Both hardness and elastic modulus of the coated samples decrease with Mg addition in the HAP-Si structure. Both Mg and Si addition into HAP coatings were found to enhance the corrosion resistance of the Ti6Al4V alloy in the SBF solution. Coatings with low Mg content exhibited better corrosion performance. All the coatings investigated were biocompatible, as demonstrated by SaOS-2 bone cell attachment and growth. However, cell proliferation and morphology were inferior on samples with the highest Mg content.